Primate evidence on the late health effects of early life adversity - Gabriella Conti; Christopher Hansman; James J. Heckman; Matthew F. X. Novak; Angela Ruggiero; Stephen J. Suomi (Institute for the Study of Labor (IZA), 2012)
This paper exploits a unique ongoing experiment to analyze the effects of early rearing conditions on physical and mental health in a sample of rhesus monkeys (Macaca mulatta). We analyze the health records of 231 monkeys which were randomly allocated at birth across three rearing conditions: Mother Rearing, Peer Rearing, and Surrogate Peer Rearing. We show that the lack of a secure attachment relationship in the early years engendered by adverse rearing conditions has detrimental long-term effects on health which are not compensated by a normal social environment later in life.
Keywords: I12; J13; 330; rhesus monkeys; health; maternal behavior; social deprivation; Tier; Familiensoziologie; Gesundheit